AB0095 Endothelial protein c receptor associated invasiveness of rheumatoid synovial fibroblasts is driven by group v secretory phospholipase a2. (23rd January 2014) - Xue, M.; Shen, K.; McKelvey, K.; Juan Li, J.; A. Chan, Y.-K.; Hatzis, V.; March, L.; Little, C. B.; Tonkin, M.; Jackson, C. J.
Abstract : Objectives: To investigate the expression and function of endothelial protein C receptor (EPCR) on synovial fibroblasts (SF) from patients with rheumatoid arthritis (RA). Methods: Human SF were isolated from synovial tissues with RA or osteoarthritis (OA) and treated with siRNAs/blocking antibody to EPCR, activated protein C (APC), tumor necrosis factor (TNF)-a, group V secretory phospholipase A2 (sPLA2 V) or co-incubated with human articular cartilage. Cell proliferation and migration/invasion were measured by MTT and collagen gel assays, respectively and cartilage degradation by glycoaminoglycan release. Cytokines, EPCR, MAP kinases, nuclear factor (NF)-kB and cadherin-11were detected by ELISA, RT real time PCR, Western blot or immunostaining. Results: EPCR was expressed by both OASF and RASF but was markedly increased in RASF. When EPCR was inhibited by siRNA or blocking antibody, cell growth, invasion and cartilage degradation were reduced by more than 30%. In addition, interleukin (IL)-1β, cadherin-11 and activation of ERK, p38, JNK and NF-kBwere significantly reduced in both control and TNF-astimulated conditions. Further analysis revealed that sPLA2 V was expressed by RASF and blocked APC binding to RASF. Suppression of sPLA2 Vreduced cell proliferation and cartilage degradation. However, when EPCR and sPLA2 V were inhibited together, the abilityof RASFto suppress cartilage degradation was abolished indicating that EPCR-associated cartilage degradation is driven by sPLA2 V. Conclusions: Our results demonstrate that EPCR is over expressed by RASF. Suppressing EPCR inhibits the invasion, inflammation and cartilage degradation by RASF. This function of EPCR, which is contrary to its cytoprotective role in other settings, is likely driven by sPLA2 V. Disclosure of Interest: None Declared